CliffsQuickReview Spanish II - Rodriguez, Jill (Wiley, 2003)
Paperback: 256 pages Publisher: Cliffs Notes (March 3, 2003) ISBN: 0764587587 Why CliffsQuickReview Guides? Go with the name you know and trust. Get the information you need?fast! Written by teachers and educational specialists. About the contents: Parts of Speech. Adjectives and comparisons. Prepositions. Pronouns. Conjunctions. Verb Review. Present tense indicative. Past tenses. Future and conditional tenses. The perfect tenses. Subjunctive indicators. Present and past subjunctive forms. The imperative. Past subjunctive and sequence of tenses. Verb charts. Vocabulary. Antonyms, synonyms, and false cognates. Glossary. Putting it Together. Spelling and pronunciation. Sentence and question structure. Review and Resources. Handy pocket guide to key concepts. Special review section to reinforce learning. Resource Center with Web sites and ideas for further study. We take great notes?and make learning a snap